Pelatihan dan Pendampingan Pendaftaran Merek Produk bagi Pelaku Usaha Mikro Kecil Menengah (UMKM) di Batam - Jarti, Nanda; Hasibuan, Rizki Prakasa; Rizki, Sestri Novia (PUAN INDONESIA, 2024)
Intellectual Property Rights (IPR) serve as legal protection for the creative and innovative rights held by Micro, Small, and Medium Enterprises (MSMEs). However, awareness and understanding of the importance of IPR registration remain low among MSMEs, who perceive the process as complex and challenging. The aim of this activity is to provide better understanding to MSMEs in Batam regarding the importance of IPR in safeguarding their products and enhancing their skills in using IPR registration applications provided by the Ministry of Law and Human Rights. The community engagement approach is utilized in this research. Socialization on the importance of IPR for MSMEs is conducted, along with direct assistance in the IPR registration process, particularly for product trademarks, through applications provided by the Directorate General of Intellectual Property. This activity demonstrates an improvement in understanding and skills among MSMEs in Batam regarding IPR. Training participants experience enhanced comprehension of IPR registration mechanisms and are able to confidently use relevant applications. Through community engagement, it can be concluded that socialization and direct assistance in IPR registration can help raise awareness and skills among MSMEs in protecting their intellectual property rights. These measures are crucial to ensure adequate protection of innovation and creativity at the MSME level, which in turn can support economic growth and sustainable development.